Competitiveness and Legitimation: The Logic of Companies going Green in Geographical Clusters - Martínez-del-Río, Javier (Journal of business ethics, 2014)
This study analyzes the logic behind the development of environmental responsiveness in companies that are located in geographical clusters. Drawing on previous research, we contend that competitiveness and legitimation are important sources of variation in these companies’ environmental responses. In particular, the companies’ perceived rivalry, competition tracking capabilities, interaction with industry associations and network embeddedness influence their competitiveness and legitimation motivations for environmental responsiveness. We used structural equation modeling to test these hypotheses on a sample of 251-clustered agricultural firms in Spain. The results support the hypotheses and provide a number of insights about the underlying motivations behind going green in geographical clusters.